HUBUNGAN POSISI KERJA DENGAN KELUHAN MUSKULOSKELETAL PADA UNIT PENGELASAN PT. X BEKASI - Jalajuwita, Rovanaya Nurhayuning; Paskarini, Indriati (Universitas Airlangga, 2015)
ABSTRACTThis study was conducted to analyze the relation between body position with musculoskeletal complaints in welding unit of PT. X Bekasi. Welding is an important part of a steel fabrication company. Workers in the welding influenced by the position of work, the posture of their body of work and performance at work. Jobs that forced the labor to not an ergonomic posture when working cause workers had faster experience fatigue and indirectly provide additional workload. Health effects that arised as a result of an unergonomic worked postures are musculoskeletal disorders .This research is an observational research with cross sectional approach design. 32 workers were chosen as sample by using simple random sampling technique. Data were obtained by measuring, observing used Rapid Entire Body Assessment (REBA), and filling out questionnaire Nordic Body Map (NBM). Spearman rho correlation test was used to analyse the relation between variables. As many as 68.6% workers had a weak risk of having musculoskeletal disorder (REBA score of 4-7) and 62.5% workers had a weak level of musculoskeletal complaint. Based on the results of this study concluded that body position were significantly related to musculoskeletal complaints. There was a weak significant relationship between body position and musculoskeletal complaints (pvalue= 0.005). It is suggested to companies that provide training on ergonomic working position when welding perform.Â Keywords: Rapid Entire Body Assessment (REBA), Nordic Body Map (NBM), body position and musculoskeletal complaints